2008
DOI: 10.1080/09553000802460180
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular S-factors for low-energy electrons: A comparison of Monte Carlo simulations and continuous-slowing-down calculations

Abstract: The use of the CSDA methodology may be unsuitable for the sub-micron scale where a more realistic description of electron transport becomes important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…André et al (2014) determined cellular S-values for I-131, I-132, I-133, I-134, I-135 and monoenergetic sources using Geant4-DNA and compared results with other Monte Carlo codes. The Geant4-DNA results were found to be in good agreement with the data obtained using other Monte Carlo codes like CELLDOSE (Champion et al, 2008) (difference up to 8%), MC4V (Emfietzoglou et al, 2008) (difference up to 4%), PENELOPE (Salvat et al, 2008) (difference up to 4%), MCNP (Cai et al, 2010) (difference up to 10%), and EGSnrc (Kawrakow, 2000) (difference up to 7%). Fourie et al (2015) employed Geant4-DNA to calculate S-values in spheres for I-123.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…André et al (2014) determined cellular S-values for I-131, I-132, I-133, I-134, I-135 and monoenergetic sources using Geant4-DNA and compared results with other Monte Carlo codes. The Geant4-DNA results were found to be in good agreement with the data obtained using other Monte Carlo codes like CELLDOSE (Champion et al, 2008) (difference up to 8%), MC4V (Emfietzoglou et al, 2008) (difference up to 4%), PENELOPE (Salvat et al, 2008) (difference up to 4%), MCNP (Cai et al, 2010) (difference up to 10%), and EGSnrc (Kawrakow, 2000) (difference up to 7%). Fourie et al (2015) employed Geant4-DNA to calculate S-values in spheres for I-123.…”
Section: Introductionsupporting
confidence: 80%
“…Ftáčniková and Böhm (2000) computed cellular S-values for several Auger emitting radionuclides using the Monte Carlo code ETRACK (Ito, 1987) and reported moderate differences (between À 18% and 21%) against the convolution integral approach. In a more detailed investigation of the validity of the CSDA, Emfietzoglou et al (2008) calculated cellular S-values for monoenergetic sources from 100 eV to 10 keV and water spheres with radius from 5 nm to 1 μm by both the convolution integral method and the Monte Carlo method using their in-house Monte Carlo code MC4 (Emfietzoglou et al, 2000). Significant differences between the two methods were found only when electron penetration depth was comparable to the size of sphere.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MCNP is capable of modeling the radiation absorbed dose to the cell nucleus (micrometer scale) from Auger electron-emitting radiotherapeutic agents that are not intimately associated with DNA. To model the dose to DNA at the nanometer scale for DNA-binding radiotherapeutics such as 125 I-iododeoxyuridine, a detailed history Monte Carlo code that follows the transport of electrons down to 100 eV would be necessary (27). Other methods, such as the inner shell ionization model, have been proposed (28).…”
Section: Discussionmentioning
confidence: 99%
“…This tool, however, has several limitations related mainly to simplified biological assumptions (e.g., spherical cell geometry lacking a physical membrane, unit density, and uniform activity distributions) and a semi-analytical radiation transport model adopting the continuous-slowing-down approximation (CSDA), thus neglecting electron straggling and secondary electrons. Indeed, other authors made use of pre-calculated Dose Point Kernels [6,7] or direct Monte Carlo radiation transport [8][9][10], pointing out the discrepancy with MIRDcell, specifically for the low energy range of electrons [11]. Moreover, it was demonstrated that asymmetries in the geometry [12,13], as well as non-concentric cell and nucleus morphology [14] significantly impact the absorbed dose to the nucleus.…”
Section: Introductionmentioning
confidence: 99%